Pseudoaneurysm of the Pancreaticoduodenal Artery Complicated by Obstructive Jaundice: A Clinical Case - Ekaterina Bakulina; Anzor Muratovich Bairamkulov; Anastasia Khodyreva (Digital Diagnostics, 2026)
Aneurysms and pseudoaneurysms of the pancreaticoduodenal arteries are relatively rare and account for approximately 1-2% of all visceral artery aneurysms. Moreover, their prevalence in the general population is even lower, estimated at about 0.009%. It should be noted that the most common risk factors for the development of pseudoaneurysms in this location are acute and chronic pancreatitis, which are relatively common among the Russian population, particularly in middle-aged men. This vascular pathology is extremely dangerous and is considered an emergency condition requiring urgent endovascular intervention. It is associated with a high risk of rupture and a mortality rate of up to 90% in the absence of timely diagnosis and treatment. Currently, the main challenge in the management of this condition is the absence of specific early symptoms prior to rupture. Additional difficulties arise from its differential diagnosis at the early stages of examination, as well as insufficient clinical awareness due to the rarity of this pathology. Modern treatment options include conservative management, surgical intervention, and endovascular procedures.We present a clinical case of a 45-year-old man with a history of chronic pancreatitis complicated by pancreatic necrosis and the development of a pseudoaneurysm of the superior pancreaticoduodenal artery, resulting in pancreatic and hepatobiliary hypertension. The patient complained of fatigue, weight loss, decreased appetite, and jaundice. Upon emergency admission to the surgical department, a preliminary diagnosis of a malignant tumor of the pancreatic head was established, which corresponded to the patient’s clinical and anamnestic data. However, subsequent computed tomography and magnetic resonance imaging performed at the oncology center revealed a large pseudoaneurysm of the pancreaticoduodenal artery, which was responsible for the patient’s symptoms. The patient was referred to vascular surgeons to determine the treatment strategy and for further follow-up.The analysis of this clinical case demonstrates that pseudoaneurysm of the pancreaticoduodenal artery is a rare but life-threatening condition that lacks specific clinical manifestations at early stages and when the lesion is small. Furthermore, this pathology often mimics other diseases, which may delay timely diagnosis and treatment and thereby pose a serious threat to the patient’s life.